Hydrogen storage alloys/reduced graphite oxide: an efficient hybrid electrode with enhanced high-rate dischargeability. (10th May 2016) - Li, M.M.; Yang, C.C.; Chen, L.X.; Jiang, Q.
Graphical abstract: In this work, we report a top-down route for preparation of uniform hydrogen storage alloys supported on reduced graphite oxide (HSAs/RGO). The as-prepared hybrid composites show enhanced high-rate dischargeability performance. Highlights: Uniform hydrogen storage alloys supported on reduced graphite oxide were prepared. The top-down fabrication strategy of the composites is effective. HSAs/RGO hybrid electrodes show enhanced high-rate dischargeability performance. The mechanisms behind enhanced high-rate dischargeability performance are revealed. Abstract: The main challenge of applications of nickel metal hydride batteries in high power fields, new-energy vehicles, power tools, military devices, etc., originates from poor high-rate dischargeability of their negative electrode material—hydrogen storage alloys (HSAs). Here we report the design and synthesis of a composite by coating HSAs with reduced graphite oxide (RGO) via a top-down route. The capacity retention rate of the fabricated HSAs/RGO hybrid electrode reaches 51.25% at a discharge current density of 3000 mA g −1, which is almost 4 times that of bare HSAs electrode (13.51%). Such an enhanced high-rate dischargeability performance is caused by (1) high specific surface area of RGO to increase active sites; (2) high conductivity of RGO to accelerate the charge transfer rate; and (3) unique interconnected RGO sheets among HSAs to reduce the internal resistance.